Monosynaptic restriction of the anterograde herpes simplex virus strain H129 for neural circuit tracing. Issue 5 (6th January 2023) - Fischer, Kyle B.; Collins, Hannah K.; Pang, Yan; Roy, Dheeraj S.; Zhang, Ying; Feng, Guoping; Li, Shu‐Jing; Kepecs, Adam; Callaway, Edward M.
Abstract: Identification of synaptic partners is a fundamental task for systems neuroscience. To date, few reliable techniques exist for whole brain labeling of downstream synaptic partners in a cell‐type‐dependent and monosynaptic manner. Herein, we describe a novel monosynaptic anterograde tracing system based on the deletion of the gene UL6 from the genome of a cre‐dependent version of the anterograde Herpes Simplex Virus 1 strain H129. Given that this knockout blocks viral genome packaging and thus viral spread, we reasoned that co‐infection of a HSV H129 ΔUL6 virus with a recombinant adeno‐associated virus expressing UL6 in a cre‐dependent manner would result in monosynaptic spread from target cre‐expressing neuronal populations. Application of this system to five nonreciprocal neural circuits resulted in labeling of neurons in expected projection areas. While some caveats may preclude certain applications, this system provides a reliable method to label postsynaptic partners in a brain‐wide fashion. Abstract : Identification of synaptic partners is an essential task for systems neuroscience. Here we present a tool for cell‐type specific anterograde monosynaptic tracing utilizing the predominantly anterograde HSV strain H129. The knockout of the capsid portal protein UL6 from a previously derived cre‐dependent version of HSV H129 prohibits genome packaging and production of infectious particles. Rescue of this knockout by expression of UL6 from a cre‐dependent AAV allows for production of infectious HSV particles that travel to downstream synaptic partners, but no further. We detail the application of this system in five non‐reciprocal neural circuits and caveats important for perspective users.